PROBLEM-BASED INSTRUCTION IN THE TEACHING OF SPEAKING (RETAIN, 2013)
Problem-Based Instruction in The Teaching of Speaking1PROBLEM-BASED INSTRUCTION IN THE TEACHING OF SPEAKINGAnggia Oktavianti A. dan SusantoS1- English Education, Language and Art Faculty, Surabaya State UniversityAbstractProblem-Based Instruction (PBI) is a learner-centered educational method in which students work in groups to solve the problem. Teacher’s role and responsibilities in Problem-based instruction method are different. The teacher acts as resource, facilitator and evaluator of students’ accomplishment. The teacher does not simply present information or directly control the progression of work. Instead, the teacher provides students with appropriate problems to work on, assists them in identifying and accessing the materials and equipment necessary to solve the problems, gives necessary feedback and support during the problem solving process, and evaluates students’ participation and products, with the goal of helping them develop their problem-solving as well as their language and literacy skills. This research aims to describe the teacher activities when she acts as a resource of students’ accomplishment, the teacher activities when she acts as a facilitator of students’ accomplishment. It is also aims to describe the teacher activities when she acts as an evaluator of students’ accomplishment. The researcher chose descriptive qualitative as the research design because the subject of this study is to describe the activities of the teacher during the implementation of Problem-based instruction and there is no treatment in this study. The researcher concentrated on one of English teacher who teach in a high school in countryside. The data in this study are the result of observation field note and interview. The data are analyzed descriptively to answer the research questions. The writer wrote all information about everything happen during the teaching-learning process in the form of long note. The writer also combined the observation method with the interview to avoid bias and subjectivity in collecting the data. The result of observation showed that the teacher activities were in line with theories about the activities of the teacher in the Problem-based instruction method. Based on the finding of data analysis and discussion, the researcher drew a conclusion: First, the teacher did her role as a resource of students’ accomplishment, second, the teacher did her role as a facilitator of students accomplishment and the third she also did her role as an evaluator of students accomplishment.Keywords: Problem-based instruction, speaking, narrative textINTRODUCTIONProblem-Based Instruction (PBI) is a learner-centered educational method. Problem-based instruction was described as learning approach that students do an authentic problem to arrange their own knowledge, to develope inquiry and the higher thinking process, and to develope self confidence independently (Arends in Triyanto, 1997). There are five stages in implementation of Problem-Based Instruction, the stages are: pre-teaching, introduce problem and vocabulary, grouping students and provide resource, observe and support, follow up and assess progress.In pre-teaching stage, the teacher explains the learning goal and make sure that the students already understand the goal and benefits of a Problem-based instruction. In the second step that is introduce problem and vocabulary, the teacher should introduce students to the problem and vocabulary related to the problem. In the third stage, the teacher divided the students in group and allowed the student to assess some resources. In the observe and support stages, teacher observe and provide support as needed, provide feedback on student participation in the activity also required in this stage. In the last stage, the teacher provides students with opportunities to present the results of their work, assessing student’s participation also required in this stage.In Kumalasari study (2011), which was conducted to know the implementation of the Problem-based instruction (PBI) to teach writing analytical exposition in eleventh graders, the result of the study showed that the content of the students’ composition were knowledgeable toward the issue or topic. The generic structure of the composition were logical sequencing. And in applying the language use, most of composition only made a few errors of agreement, tense, nouns, relating verb.Speaking is an essential skill for English learner as a foreign language alongside listening, reading, and writing in the process of learning. Despite its importance, applying an interactive teaching method is necessary. So that, teacher keep applying and developing method in teaching-learning process. However, most of student still think that speaking is difficult. According toProblem-Based Instruction in The Teaching of Speaking2Rivers (1968:192) there are some factors why the students prefer to keep silent in the class. First, they are afraid of making mistakes and the second is student are usually bored with the classroom activity. That’s why the teacher has to find a good approach, method, or technique to teach their students. With an appropriate method, teacher will teach the student successfully. One of the methods that can be used to overcome this problem is using Problem Based Instruction method (PBI).Several teachers in Indonesia has implemented this method. One of them is an English teacher in one of public Sunior High School in Jombang. She has implemented the method to teach speaking to her students. She has been successful in implementing Problem-Based Instruction method for the teaching speaking to her students. By using this method, the students encounter a problem and try to solve it with information they already possess allowing them to appreciate what they already know. They also identify what they need to learn to better understand the problem and how to resolve it.From the information above, the researcher decides to conduct same research like previous researcher did but different in skill, text and problem. She will analyze about the implementation Problem-based instruction in teaching speaking at senior high school. She also concern to know more about what are the teacher role during Problem-Based Instruction method in speaking class. It is to know the teacher’s activities when she acts as a resources,a facilitator, and an evaluator of students accomplisment.METHODOLOGYResearch DesignThe study was designed as a descriptive qualitative research. According to Susanto (2002: 36) descriptive research is a research in which the researcher has to describe and interpret the events happened in detail. It means that descriptive qualitative research describes what exist in reality, which involves the description, recording, analysis and interpretation of the condition of that exist.Subject of the StudyThe subject of the study were an English teacher who teach in a high school of a countryside. The researcher chose the subject because one of the teacher had implemented Problem Based Instruction (PBI) in the teaching speaking in her class.Data and source of the dataData are certain information used as the basis material of the analysis to get the answer of the research questions. There were two kinds of qualitative data to answer the research questions of this study. The first data were the description of teacher’ expressions, comments and behaviors which show her activities as a resource in Problem based instruction method. These data were used to answer the first research question “what are the teacher’s activities when she acts as a resource of students accomplishment during the implementation of PBI method?”.The second data were the description of teacher’ expressions, comments and behaviors which show her activities as a facilitator in Problem-based instruction method. These data were used to answer the second research question “what are the teacher’s activities when she acts as a facilitator of students’ accomplishment during the implementation of PBI method?”The third data were the description of teacher’ expressions, comments and behaviors whether it is verbal or non-verbal during the teaching learning process (1). These showed her activities as an evaluator of students accomplishment in Problem based instruction method. These data were used to answer the third research question “what are the teacher’s activities when she acts as an evaluator of students accomplishment during the implementation of PBI method?” The researcher also took the teacher’ responses by giving interview. The questions of the interview related to the teaching and learning process. The result of the interview will be used to support the main data. The sources of data for this study were the students who followed the teaching and learning process.Data Collection TechniqueIn this study the writer collected the data through observation since this study is categorized as a qualitative research. Observation is the process of gathering open-ended first-hand information by observing people and places to record information as it occurs and to study actual behavior at a research site (craswell:210). The writer used field note observation. Bogdan and Biklen (in Moleong 2005: 209) stated field note is written note about what was heard, seen, thought and had been around in order to collect as well as reflect the data in qualitative research. The writer wrote all information about everything happen during the teaching-learning process in the form of long note. The writer also combined the observation method with the interview to the teacher to avoid bias and subjectivity in collecting the data.Problem-Based Instruction in The Teaching of Speaking3Data Analysis TechniqueThe result of the data was analyzed descriptively. The researcher tend to write all information that she saw and heard. According to Susanto (2008:56) there are four steps to analyze the observation data, they are as followed:1. Classifying the dataIn observation field notes, the data are teachers’ answer in the form of utterances, and expressions spoken/given by the teachers during interview sessions which are transcribed into written form. These data should be classified into some titles which are represented the data classification in order to make it easier to be read and understood.2. Separating the dataAfter the data were classified into some titles, the researcher separates the relevant and irrelevant data with the research problems. The relevant data will be analyzed to the next steps. In this step the researcher should have mind mapping to organize and to compose chapter IV based on research problem.3. Synthesizing the dataIn this study the data was collected by one observer with different methods, observation and interview. There will not appear any significant different in both data because the use of second method is to find the correct data of the first method. Both of the data are synthesized to find out the similarity and the different.4. Reporting the dataIn the previous steps are the steps where the researcher starts to compose the report. All the findings, discussion and conclusion are inductively composed as the answers of the research problems of chapter one.RESULTS AND DISCUSSIONThe implementation of Problem-based instruction in the teaching speakingThe data were obtained through the observation that was focused in the teachers’ activities during the implementation of Problem-Based Instruction. The implementation of Problem-Based Instruction method was divided into five stages, they are pre teaching, introducing problem and vocabulary, group students and provide resource, observe and support, and the last was follow up and assess progress. Before the teacher implemented the problem-based instruction method, she explained the material about narrative text. In the beginning of the class, the teacher greeted the students, asked about their condition and checked the attendance list. The teacher explained to the students about what they were going to do for the lesson that day. She read the basic competence and the learning objective for them. It was purposed to ensure that all the students knew what they needed to achieve at the end of the study. After giving explanation about the basic competence, and the learning objectives the teacher gave apperception for the students related to the goal they wanted to achieve. Teacher started the lesson by reviewing about narrative text that students have learned in the first grade. She also gave some explained about the Problem-based instruction method before she apply in the class activity. This was done by the teacher to make her students understand about the method that the teacher will apply. Therefore, they will easier in the next activity.The teacher activities as a resource of students’ accomplishmentThe results of the observation show that the teacher did some activities; they were guidance as to where students can go to look for information, encourage students to use resource material for themselves and to become more independent in the learning generally. When the students asked about something they didn’t understand. The teacher explained it clearly therefore, the student know what is that exactly. And the teacher took part by giving the correct pronunciation to the students, therefore, the students became understood how to pronounce those words.The teacher also help the student to know where they can find the information that they want to know. There was a student asked about difficult words and she let the student to take a look on the dictionary first and then she also let the student find it in the teacher dictionary. She didn’t give the answer directly because she knew exactly that her job here was guiding the students. Harmer (2007: 110) states that when we are acting as a resource, we will want to be helpful and available, but at the same time we have to resist the urge of spoonfeed our students so that they become over reliant on us. As a resource does not mean that the teacher should give all the answer without any recommendation, teacher should guide them so that they can find the answer by themselves.Teacher activities as a facilitator of students’ accomplishmentProblem-Based Instruction in The Teaching of Speaking4Based on results which are gained from the analysis data, the researcher concluded that the teacher did some activities began from made sure students understand the goals and benefits of a problem based approach for language learning. The teacher introduced the problem using text eventhough she did not introduce vocabulary related to the problem since the problem different, she also group students and give students access to resources, and while the students are working in their group, she walked around the class and visited each group. She gave feedback helpful and meaningful on students. According to Gentry (2000:11) “teacher have a huge responsibility because they are the first point of contact with their students and have a tremendous influence over the way they learn.” The giving up of support and observe the class are the part of problem-based instruction thatthe teacher usually struggle with the most. However, support by the teacher made the learning better in the activity. At last, the teacher also provided the students opportunities to perform their result and gave some critics and suggestion to the groups’ performance.Teacher activities as an evaluator of students accomplishmentThe results of observation which show that the teacher did her role as an evaluator. The teacher gave some critics and also provides suggestion to each groups’ performance. As an evaluator the teacher should assess the students’ performance. As Zeiger (2000) in chapter two stated that teacher also play the role of evaluators, constantly assessing students’ abilities through formal and informal assessments, providing suggestions for improvement and assigning grades. After the groups’ performance, she always gave her critics and also suggestion.CONCLUSIONThe major problem of this study is the teachers’ activity during the Problem-instruction method. The main problem that is developed based on the teacher activity during the problem instruction divided into three, they are: (1) the teacher activities as a resource of students’ accomplishment, (2) the teacher activities as a facilitator of students’ accomplishment, (3) the teacher activities as an evaluator of students’ accomplishment.Based on the findings of data analysis and discussion in the previous chapter, the researcher drew a conclusion: first, the teacher did her role as a resource of students’ accomplishment. The teacher guidance as to where students can go look for that information and encourage students to use resource material for themselves and to become more independent in their learning generally. Second, the teacher did her role as a facilitator of students’ accomplishment. Her activities as a facilitator began from pre-teaching, introduced problem and vocabulary, group students and provided resource, observed and support the groups’ working, follow up and asses progress. And the third was the teacher did her role as an evaluator of students’ accomplishment. The teacher gave students critics after each groups’ performance about their pronunciation, action, she also provide suggestion for each group performance for improvement and finally, she developed rubric in evaluating students’ performance.SUGGESTIONAt the end of this study, some suggestions are offered related to the result of the study. The result of this study was that the teacher did her role as a resource of students’ accomplishment, facilitator and evaluator of students’ accomplishment, but to become a professional teacher she also must have the other aspect, having a good teaching skill. Therefore first, the researcher suggest to the teacher to design more authentic problem with the propose of promotes meaningful interaction in the classroom. Second, the researcher suggest to the teacher to consider about language use that she choose. Third, the researcher suggests to other researchers to conduct a similar study, but they can view from the other aspects such as the grade levels of education, and various type of genre.REFERENCESAnderson & Anderson. (2003). Text Types in English. South Yarra: Macmillan.Barrows, H (1985). How to design a Problem-Based Curriculum for the Pre Clinical Yaers. NY: Springer.Boothe, Diane. 2007. The Future of Education: Innovative English Language Acquisition Through Problem-Based Learning.Brown, H. Douglas. 2007. Teaching by Principles: An Interactive Approach to Language Pedagogy. Third Edition. New York: Longman Inc.Chaney, A.L., and T.L. Burk. 1998. Teaching Oral Communication in Grades K-8. Boston: Allyn&Bacon.Disick ,Renee S and M. Valette,Rebecca. 1972. Modern Language Performance Objectives and Individialization a Handbook. New York: Harcout Brace Jovanonich, Inc.Problem-Based Instruction in The Teaching of Speaking5Engel, C E (1991) Not just a method but a way of learning; pp 23-33 in Boud, D & Feletti, G (eds) The Challenge of Problem-Based Learning. London: Kogan page.Gentry, F (2000) Creating Student Centered , Problem-based classroom. In (Ed), (p). Huntsville: University of Alabama in Huntsville Retrieved August 10, 2013, from http://aspire.cs.uah.edu/Harmer, Jeremy. 2007. The Practice of English Language Teaching. Fourth Edition. Harlow : UK: Pearson Education Limited.Kumalasari, vivi shantya. 2011. Problem Based Instruction (PBI) IN Teaching Writing Analytical Exposition Text for Eleventh GradeStudents. Unpublished Thesis. Universitas Negeri Surabaya.Mathews-Aydinli, J. (2007). Problem-Based Learning and Adult English Language Learners. In Center of Adult English Language Acquisition (CAELA). Washington, DC: Center for Applied Linguistic.McDonald, D & Isaacs, G (2001) Developing a professional identity through problem-based learning. Teaching Education. 12 315-333.Moleong, J. Lexy. 2005. Metodologi Penelitian Kualitatif. Bandung: PT Remaja Rosdakarya.Rivers, M. Wilga. 1983. Speaking in many Tongues: Essays in Foreign Language Teaching Third Edition. New York: Cambridge University Press.Susanto. 2002. Develpoing a research proposal (a Practical Guideline). Universitas Negeri Surabaya.Trianto (2007), Model-model Pembelajaran Inovatif Berorientasi Konstruktivistik: Jakarta: Prestasi Pustaka.